Consequences of canceling elective invasive cardiac procedures during Covid‐19 outbreak. Issue 5 (17th December 2020) - Moreno, Raúl; Díez, José‐Luis; Diarte, José‐Antonio; Macaya, Fernando; de la Torrre Hernández, José‐María; Rodríguez‐Leor, Oriol; Trillo, Ramiro; Alonso‐Briales, Juan; Amat‐Santos, Ignacio; Romaguera, Rafael; Díaz, José‐Francisco; Vaquerizo, Beatriz; et al.
Abstract: Background: During COVID‐19 pandemic in Spain, elective procedures were canceled or postponed, mainly due to health care systems overwhelming. Objective: The objective of this study was to evaluate the consequences of interrupting invasive procedures in patients with chronic cardiac diseases due to the COVID‐19 outbreak in Spain. Methods: The study population is comprised of 2, 158 patients that were pending on elective cardiac invasive procedures in 37 hospitals in Spain on the 14th of March 2020, when a state of alarm and subsequent lockdown was declared in Spain due to the COVID‐19 pandemic. These patients were followed‐up until April 31th. Results: Out of the 2, 158 patients, 36 (1.7%) died. Mortality was significantly higher in patients pending on structural procedures (4.5% vs. 0.8%, respectively; p < .001), in those >80 year‐old (5.1% vs. 0.7%, p < .001), and in presence of diabetes (2.7% vs. 0.9%, p = .001), hypertension (2.0% vs. 0.6%, p = .014), hypercholesterolemia (2.0% vs. 0.9%, p = .026) [Correction added on December 23, 2020, after first online publication: as per Dr. Moreno's request changes in p‐values were made after original publication in Abstract.], chronic renal failure (6.0% vs. 1.2%, p < .001), NYHA > II (3.8% vs. 1.2%, p = .001), and CCS > II (4.2% vs. 1.4%, p = .013), whereas was it was significantly lower in smokers (0.5% vs. 1.9%, p = .013). Multivariable analysis identified age > 80, diabetes, renal failure and CCS > II as independent predictors for mortality. Conclusion: Mortality at 45 days during COVID‐19 outbreak in patients with chronic cardiovascular diseases included in a waiting list due to cancellation of invasive elective procedures was 1.7%. Some clinical characteristics may be of help in patient selection for being promptly treated when similar situations happen in the future.